Falas Waikhana: conhecimento e transformações no alto rio Negro (rio Papuri) - Silva, Aline Scolfaro Caetano da (Universidade Federal de São Carlos, 2012)
Result of an ethnographic research among the Waikhana (Pira-Tapuia), a Tukanoan group that lives around the Uaupes basin, Amazonian Northwest, this dissertation focuses on hierarchy and circulation of knowledge in Uaupes contemporary context. This context is characterized by what has been called by the indigenous groups as culture recovery and revitalization movement . Involved in this local dynamics, the Waikhana attempt to recover by one side some ritual practices and traditional techniques of environment handling and by the other side the written record of certain oral knowledge in former times updated and transacted in ritual occasions. Trying to understand the way the indigenous are experiencing those processes and emphasizing their developments in the sphere of their own sociopolitical relations, this text approaches some classical themes on regional literature concerning social organization and cosmology. Some interpretations and redirections made by the indigenous themselves, concerning the problematic of hierarchy and circulation of knowledge will be presented. And will show that these interpretations and redirections bring some relations and positions of a Waikhana (cosmos) politics up to date.
Keywords: Etnologia; Índios da América do Sul; América do Sul, Noroeste Amazônico; Amazônia - povos tukano; Pira-tapuia; Conhecimento; Hierarquia; Cosmopolítica; Amazonian Northwest; Tukanoan; Pira-Tapuia; Knowledge; Hierarchy; Cosmos-politics; CIENCIAS HUMANAS::ANTROPOLOGIA